2019
DOI: 10.3389/fbioe.2019.00024
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Engineered Crops: Importance of Diversified Integrated Pest Management for Agricultural Sustainability

Abstract: As the global population continues to expand, utilizing an integrated approach to pest management will be critically important for food security, agricultural sustainability, and environmental protection. Genetically engineered (GE) crops that provide protection against insects and diseases, or tolerance to herbicides are important tools that complement a diversified integrated pest management (IPM) plan. However, despite the advantages that GE crops may bring for simplifying the approach and improving efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(65 citation statements)
references
References 74 publications
0
65
0
Order By: Relevance
“…Apart from physical and chemical approaches, several other methods such as modification in breeding practices, shifting of crop calendars and introduction of genetically engineered salt-tolerant plant varieties have been evaluated for enhancement of crop productivity in salt-affected soils but have largely proved to be in-effective [19] , [20] . These methods are time-consuming, costly and above all, cause genetic erosion of indigenous species [21] , [22] .…”
Section: Introductionmentioning
confidence: 99%
“…Apart from physical and chemical approaches, several other methods such as modification in breeding practices, shifting of crop calendars and introduction of genetically engineered salt-tolerant plant varieties have been evaluated for enhancement of crop productivity in salt-affected soils but have largely proved to be in-effective [19] , [20] . These methods are time-consuming, costly and above all, cause genetic erosion of indigenous species [21] , [22] .…”
Section: Introductionmentioning
confidence: 99%
“…8,9 In the future, the discovery and deployment of novel GE toxins targeting new insect orders will be important to further reduce yield losses, protect farmer profit, and minimize environmentally disruptive pesticide use. 10 Bayer has developed MON 88702 cotton, the first crop that expresses Cry51Aa2.834_16 Bt toxin to control targeted hemipteran and thysanopteran crop pests. 11,12 The Cry51Aa2.834_16 Bt toxin (hereafter referred to as MON 88702) expressed in cotton was modified to selectively enhance insecticidal activity against piercing-sucking pests.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, the production of all of these antibiotic and insecticidal compounds suggests that B. amyloliquefaciens ZJU1 is a good candidate for the development of biocontrol strategies against emerging gray mold-related infectious diseases and notorious lepidopteran pests, for instance, through artificial inoculation of the soil/rhizosphere or seeds/seedlings and direct injection into plant tissues. Considering the complete genome sequence reported here and its amenability to genetic manipulation, ZJU1 could be further engineered to increase plant performance, as it was recently shown that engineering of the banana endosphere microbiome improved Fusarium wilt resistance in banana (Anderson et al, 2019;Liu et al, 2019). Our study therefore highlights that expanding the investigation of the plant microbiome could lead to additional successful discoveries of unexplored novel microbial symbionts with biotechnological potential.…”
Section: Discussionmentioning
confidence: 75%